Post-Flash Flood Disaster Management in Limo Kaum Village, Tanah Datar Regency - Widya Lolita; Erna Juita; Rika Despica (Jurnal Geografika (Geografi Lingkungan Lahan Basah), 2025)
This research is motivated by the flash flood disaster that occurred in Nagari Limo Kaum, Tanah Datar Regency. This study aims to analyze: 1) Spatial distribution after the flash flood which includes the affected areas and the severity of the impact, as well as accessibility conditions. 2) Post-flash flood disaster management system which includes aspects of preparedness, mitigation, rehabilitation, and recovery. This type of research uses a mixed method that combines quantitative and qualitative. The population includes all jorong in Nagari Limo Kaum, with samples from four affected jorong. Informants were selected using Purposive Sampling. Data were collected through observation, interviews, documentation, and spatial mapping. The results of the study show 1) the distribution of flood impacts is uneven, with the highest level of damage occurring in Jorong Dusun Tuo at 7.36% of the total area. Impacts include damage to houses, agricultural land, public facilities, and disruption of accessibility between jorong. 2) the post-disaster management system has not been running optimally. Preparedness and mitigation efforts remain low, and rehabilitation focuses more on physical infrastructure, while social and psychological aspects remain largely unaddressed. Community capacity building, improved early warning systems, and better cross-sector coordination are needed for sustainable disaster management.